Pegaspargase Induced Hypertriglyceridemia Resulting in Severe Fatal Pancreatitis - Neil Vyas; Rafael Ching Companioni; Melik Tiba; Hassan Alkhawam; Aaron Walfish (Case Reports in Gastrointestinal Medicine)
Pegaspargase is used to treat acute lymphocytic leukemia (ALL). Pegaspargase definitely has its benefits in treating ALL; however we cannot lose sight of one of its very rare but potentially deadly complications, acute pancreatitis. Clinicians should monitor triglycerides while the patient is on treatment with Pegaspargase and suspect acute pancreatitis if the patient develops abdominal pain. If pancreatitis occurs, therapy should be stopped immediately and not reinstituted. For patients with hypertriglyceridemia without pancreatitis, discontinuation of therapy should be considered.